Mindfulness in kindergarteners : understanding the underlying attentional mechanism - Lim, Xinyi (2016)
According to Lutz, Slagter, Dunne and Davidson (2008), mindfulness practices can influence attention via two mechanisms, focused attention and open monitoring. Based on this framework, the current thesis investigated whether after one-session mindfulness practice focused attention and open monitoring mindfulness training can influence kindergarten children’s attention. A between- and within-subject mixed design was used. Five to six-year-old children were randomly assigned to three groups, focused attention mindfulness training, open monitoring mindfulness training, and an active control. All children underwent a 15-min practice session. In addition to a vocabulary test, before and after the practice, a battery of attention tests was administered. Results showed that focused attention and open monitoring influence children’s attention differentially. In particular, focused attention training shifted children’s visual perception towards local biasing, whereas open monitoring training improved children’s conflict monitoring. Theoretical and practical implications are discussed. Keywords: mindfulness, focused attention, open monitoring, attention